2017
DOI: 10.1128/jvi.00720-17
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of PA-X and NS1 Proteins in Replication and Pathogenesis of a Temperature-Sensitive 2009 Pandemic H1N1 Influenza A Virus

Abstract: Influenza A viruses (IAVs) cause seasonal epidemics and occasional pandemics, representing a serious public health concern. It has been described that one mechanism used by some IAV strains to escape the host innate immune responses and modulate virus pathogenicity involves the ability of the PA-X and NS1 proteins to inhibit the host protein synthesis in infected cells. It was reported that for the 2009 pandemic H1N1 IAV (pH1N1) only the PA-X protein had this inhibiting capability, while the NS1 protein did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
104
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(116 citation statements)
references
References 69 publications
(150 reference statements)
10
104
2
Order By: Relevance
“…It has been shown that multiple mechanisms are related to host shutoff in IAV-infected cells. However, recent studies have focused on the following three main mechanisms of global inhibition of host protein expression by IAV infection: (1) blockade of cellular mRNA processing and nuclear export by NS1 [16][17][18][19]; (2) degradation of host RNA Pol II by the viral RNA-dependent RNA polymerase RdRp complex (RdRP) [20][21][22]; and (3) wide-spread host mRNA degradation by the PA-X protein [11,[23][24][25][26][27][28][29][30][31]. In this review, we focus mainly on the shutoff activity of PA-X protein.…”
Section: Global Host-shutoff Activity By the Pa-x Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that multiple mechanisms are related to host shutoff in IAV-infected cells. However, recent studies have focused on the following three main mechanisms of global inhibition of host protein expression by IAV infection: (1) blockade of cellular mRNA processing and nuclear export by NS1 [16][17][18][19]; (2) degradation of host RNA Pol II by the viral RNA-dependent RNA polymerase RdRp complex (RdRP) [20][21][22]; and (3) wide-spread host mRNA degradation by the PA-X protein [11,[23][24][25][26][27][28][29][30][31]. In this review, we focus mainly on the shutoff activity of PA-X protein.…”
Section: Global Host-shutoff Activity By the Pa-x Proteinmentioning
confidence: 99%
“…When considering the role of NS1 and PA-X in viral pathogenicity and host shutoff, it is very interesting to see the combined effects of them in modulating viral virulence. Therefore, recently, Nogales et al investigated the interplay of PA-X and NS1-mediated host shutoff in viral replication and pathogenesis using a temperature-sensitive 2009 pandemic H1N1 virus [31]. These researchers found that viruses that simultaneously encode PA-X and NS1, or are deficient in both proteins, are highly attenuated in vivo, suggesting that there is a strict balance between NS1 and PA-X proteins during host gene expression regulation, viral replication, and pathogenesis.…”
Section: Concerted Effect Of Pa-x and Ns1 In Host Shutoff And Pathogementioning
confidence: 99%
See 1 more Smart Citation
“…NS1 is a multifunctional protein and a key viral factor that counteracts the host antiviral responses. NS1 has been shown to inhibit the production of interferon (IFN), the activity and expression of multiple interferon-induced genes (ISG) and the processing and nuclear transport of host mRNAs causing cellular shut-off [25,26]. Segment 3 of IAV also encodes two proteins, the polymerase component PA and PA-X.…”
mentioning
confidence: 99%
“…Synergistically with NS1, PA-X is also able to block the cellular antiviral responses by inhibiting host protein expression. Moreover, the PA-X protein has been shown to modulate host inflammation, immune responses, apoptosis, and virus pathogenesis [25][26][27][28][29][30].…”
mentioning
confidence: 99%